Potential application of Istisna’ financing in Malaysia - Hasmawati, Anisza; Mohamad, Azhar (Emerald, 2019)
Purpose – This study aims to investigate the potential application of Istisna’ financing in Malaysia. Design/methodology/approach – Using primary data from semi-structured interviews with 17 participants, including Islamic financial institutions (IFIs), regulatory body and property development companies, the findings of the study suggest that Istisna’ is perceived as a good contract that has unique features and the potential to be implemented in Malaysia; although, it has only been implemented a little by current businesses, mainly due to its perceived high risks. Findings – The authors find there is a gap between the theory and the actual operation of IFIs in Malaysia – some salient features of an Islamic contract are actually difficult to execute in reality as there are many factors to be considered, such as default risk in Istisna’, legal issues and accounting treatment of Istisna’ contract. This study recommends the further development of Istisna’ in Malaysia due to its huge potential in the Islamic financial market there. Practical implications – Istisna’ is a unique type of sale contract that is used in the manufacturing sectors where the sale of a commodity is transacted before the commodity exists. In practice, data from the Central Bank of Malaysia show that Istisna’ financing is scarce. Originality/value – The study differs from previous research studies on Istisna’ – to the best of the authors’ knowledge, this is the first study to provide evidence the real thoughts of IFIs with regard on Istisna’ specifically and IFIs’ operations in general. Previous studies related to Istisna’ have limited scopes, as they have mainly explored the theoretical nature of the contract, issues of permissibility from the Shariah perspective and its comparability with other IFIs product such as Salam. In this study, from respondents’ views, the authors notice actually there is a gap between theory and the real practice of Islamic finance. An Islamic finance instrument may be an ideal choice to customers but not very popular from IFIs’ sides. In this respect, the authors add to the growing literature of Istisna’ by asking the direct questions to IFIs and the authors get honest responses pertaining to default risk, legal issues and accounting treatment.